HUBUNGAN KECERDASAN SPIRITUAL TERHADAP STRES PADA REMAJA - Rosma, Febriana; D Mustamu Qomal Pa’ni; Aoladul Muqarrabin; Teguh Achmalona; Baiq Fitrihan Rukmana (Citra Internasional Institute, 2024)
The research aims to determine the effect of spiritual intelligence on stress in teenagers at the Nurul Hidayah prayer room. This research uses a quantitative approach with a non- experimental design. The research population was all teenagers at the Nurul Hidayah prayer room and a sample of 24 people were taken using the Slovin formula with simple random sampling technique. The data collection method used the SWBS and DASS-21 questionnaires. Data analysis used chi-square analysis. The results of this research show that there is an influence of spiritual intelligence on stress with evidence of ? value = 0.009 < ? = 0.05, so that there is a significant influence of spiritual intelligence on stress levels in Nurul Hidayah prayer room teenagers. The higher a teenager's spiritual intelligence, the lower a person's stress level.